Respuesta :

check the picture below.

[tex]\bf \textit{Law of Cosines}\\\\ c^2 = a^2+b^2-(2ab)cos(C)\implies c = \sqrt{a^2+b^2-(2ab)cos(C)} \\\\\\ \cfrac{a^2+b^2-c^2}{2ab}=cos(C)\implies cos^{-1}\left(\cfrac{a^2+b^2-c^2}{2ab}\right)=\measuredangle C\\\\ -------------------------------[/tex]

[tex]\bf s^2=r^2+t^2-2rt\cdot cos(S)\implies s^2-r^2-t^2=-2rt\cdot cos(S) \\\\\\ \cfrac{s^2-r^2-t^2}{-2rt}=cos(S)\implies \cfrac{r^2+t^2-s^2}{2rt}=cos(S) \\\\\\ cos^{-1}\left( \cfrac{r^2+t^2-s^2}{2rt} \right)=\measuredangle S\implies cos^{-1}\left( \cfrac{14^2+6^2-9^2}{2(14)(6)} \right)=\measuredangle S[/tex]

make sure your calculator is in Degree mode if you need ∡S in degrees.
Ver imagen jdoe0001
10.05 I’m pretty sure